The Rødryggen-1 and Brorson Halvø-1 fully cored boreholes (Upper Jurassic – Lower Cretaceous), Wollaston Forland, North-East Greenland – an introduction - Jørgen A. Bojesen-Koefoed; Peter Alsen; Morten Bjerager; Jussi Hovikoski; Jon R. Ineson; Peter N. Johannessen; Mette Olivarius; Stefan Piasecki; Henrik Vosgerau (GEUS Bulletin, 2023)
Two fully cored boreholes, the Rødryggen-1 and the Brorson Halvø-1, were drilled in Wollaston Forland, North-East Greenland, in 2009 and 2010, respectively. The objective was to test the stratigraphic development of the Upper Jurassic – Lower Cretaceous mud-dominated succession in two different settings within the same fault block of a developing half-graben: centrally (Rødryggen-1 borehole) and near the uplifted crest of the rotating fault block (Brorson Halvø-1 borehole). The drilled deposits are equivalent to the principal petroleum source-rock sequence of the petroliferous basins of North-West Europe, Siberia, and basins off eastern Canada and provide a new record of an important phase of marine deoxygenation in the proto-North Atlantic region.